Hubungan Konsumsi Fast Food Dan Tingkat Pengetahuan Gizi Dengan Kejadian Berat Badan Lebih Di Sma Kota Kab.Bone - Nurfadillah, Nurfadillah; Amir, Sakinah; Rahmiati, Rahmiati (Action Research Literate, 2025)
The problem of overnutrition in adolescents is a growing phenomenon in line with changes in modern dietary patterns, particularly the high consumption of fast food. This study aimed to determine the relationship between fast food consumption and nutritional knowledge levels and the incidence of overweight among high school adolescents in Bone Regency. The study used a cross-sectional design with a purposively selected sample of 49 respondents. Data on fast food consumption were obtained through questionnaires, nutritional knowledge levels were measured using a nutritional knowledge questionnaire, and nutritional status was determined based on anthropometric measurements using the BMI/Age (Z-score) indicator. Data were analyzed using the Chi-square test and Spearman correlation. The results showed a significant association between fast food consumption and the incidence of overweight (p=0.041; r=0.446) and between nutritional knowledge levels and the incidence of overweight (p=0.005; r=0.386). This indicates that the higher the frequency of fast food consumption and the lower the nutritional knowledge, the greater the risk of overnutrition in adolescents. This study recommends the importance of nutrition education and controlling fast food consumption in adolescents, as well as the active role of schools and families in fostering healthy eating behaviors to prevent overnutrition.